Home assistance and care for elderly patients in Brazil after stroke: an integrative review (Research, Society and Development, 2022)
Objective: To analyze how family care is provided to elderly patients after a stroke, the necessary care and how they are developed. Methodology: An integrative literature review based on 19 articles extracted from the PUBMED and LILACS and SCIELO Brazil databases from 2011 to 2021. Results: A high prevalence of elderly stroke victims who need continuous home care was found and who most are provided by family caregivers who have high emotional and physical burden. The necessary health care are those aimed at motor rehabilitation and recovery of functional capacity in which nurses are the main involved in this process. Conclusion: The theme addressed becomes even more important due to the epidemiological transition experienced, and it is necessary to develop effective strategies together with health networks and home care for the functional rehabilitation of these patients, strengthening family caregivers in order to ensure the physical and emotional health of all. involved in this daily life.